Guérilla et terrorisme en Amérique latine - Grenier, Yvon (Études internationales, 1988)
In this paper, we deal with the distinction between two specific forms of political mobilization in Latin America, guerrilla and terrorism. First, we try to identify and discuss the main historical events in the evolution of guerrilla mobilization. We emphasize the socio-political profile and the ideological dispositions which are usually related to the guerrilla mobilization. Then, we examine the two phenomenons in a comparative perspective. We argue that guerrilla is a form of political mobilization that entails a fundamental change in the political competition (which involves an internal war), whereas terrorism, by its scope, its goals and its objectives, may only affect, to some extent, one or many policies of a given government. Finally, we propose two definitions of guerrilla and terrorism, followed by some additional commentaries on their theoretical limits.